Integrasi Tauhid dan Etika Sosial dalam QS. Al-Nisa'/4: 36 Perspektif Tafsir Al-Misbah - Mochamad Rifal Julianto; Arif Rahman (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2026)
Ethics in daily life constitutes a fundamental foundation for establishing a harmonious and civilized society. This study aims to analyze the values of social ethics in Tafsir Al-Misbah by M. Quraish Shihab, focusing on Surah An-Nisa’/4:36. The selection of this verse is based on its comprehensive ethical content, which integrates the principle of monotheism (tawhid) as a theological foundation with commands to act kindly toward parents, relatives, orphans, the poor, neighbors, and slaves. This research employs a library research method with a qualitative-descriptive approach using content analysis. The findings reveal that M. Quraish Shihab emphasizes an organic relationship between ritual worship and social behavior. Devotion to Allah (hablun min Allah) must be manifested in concrete social actions such as compassion, humility, and inclusivity toward fellow human beings (hablun min al-nas). In conclusion, social ethics in Tafsir Al-Misbah is not merely a formal moral norm, but an integration of spirituality and humanity that is relevant in addressing the moral crisis of the modern era.